Inhuman power : artificial intelligence and the future of capitalism - Dyer-Witheford, Nick, 1951-; Kjøsen, Atle Mikkola; Steinhoff, James (Digital barricades., 2019)
"The past several years have brought staggering advances in the field of Artificial Intelligence. And Marxist analysis has to keep up: while machines were always central to Marxist analysis, modern AI is a new kind of machine that Marx could not have anticipated. Inhuman Power explores the relationship between Marxist theory and AI through three approaches, each using the lens of a different Marxist theoretical concept. While the idea of widespread AI tends to be celebrated as much as questioned, a deeper analysis of its reach and potential produces a more complex and disturbing picture than has been identified. Inhuman Power argues that on its current trajectory, AI is likely to render humanity obsolete and that the only way to prevent it is a communist revolution."--Publisher's website